Spiritual ambiguity in interfaith humanitarianism: Local faith communities, Syrian refugees, and Muslim–Christian encounters in Lebanon and Jordan. (19th July 2021) - Gutkowski, Stacey; Larkin, Craig
Abstract: Literature on faith-based responses to forced displacement has described, but not fully unpacked or theorized cross-religion humanitarian aid in 'South–South' contexts. This article interrogates the various ambiguities, particularly spiritual ambiguities, inherent in faith-based humanitarianism where local providers are the minority religion. In unpacking these, we identify three modes of faith-based aid to Muslim Syrian refugees by local churches and Christian charities in Lebanon and Jordan: hospitality, humanitarian, and spiritual development. These may present successively deeper opportunities for fostering openness to spiritual pluralism. We argue for greater appreciation of what we call spiritual ambiguity in interfaith humanitarianism. While humanitarian space is always shaped by a web of power relations, it is vital to develop new, more nuanced ways of thinking about cross-religious faith-based humanitarianism beyond Western neo-colonialism or refugee strategizing.